(untitled) (Bangladesh Journal of Child Health, 2010)
Objective: To study the predictors of intractable childhood epilepsy and to compare the predictors of outcome in early and late onset childhood epilepsy. Design: Retrospective study. Study place: Child Development and Neurology Unit in the Department of Paediatrics of Bangabandhu Sheikh Mujib Medical University (BSMMU). Study period: January 2004 to December 2005. Subjects: Children with epilepsy of 1 month to 15 years of age who attended the epilepsy clinic. Results: The predictors of outcome of childhood epilepsy were analyzed. According to outcome there were two groups, well- controlled group (seizure free for more than 6 months) and intractable epilepsy ( one or more seizures per month over a period of 6 months). The predictors of early and late onset childhood epilepsy were also compared. Total 73 cases were studied. Out of them 38 patients had early onset epilepsy (less than one year) and 35 had late onset epilepsy (more than one year). Median age of onset of early and late onset of childhood epilepsy group was 3.5 months and 60 months respectively. Male and female ratio was 1.53:1 and 0.94:1 in early and late onset group respectively. Major seizure type was tonic-clonic seizure in 57.9% and 77.1% patients of early and late onset group respectively. In this study, 27 (77.1%) patients of late onset and 5(13.2%) patients of early onset group achieved seizure remission. Independent predictors of intractable childhood epilepsy were finally found. Conclusion: In this study symptomatic epilepsy, myoclonic seizure, initial high frequency of seizure, infantile spasm, neonatal seizures and birth asphyxia were significantly higher among early onset group than in late onset group. Early onset of seizure, myoclonic seizure, initial high frequency of seizure (≥1 seizure/day), symptomatic etiology, neonatal seizure and microcephaly were found independent predictors of intractable epilepsy. Key words: Early onset; late onset; intractable seizures. DOI: 10.3329/bjch.v33i1.5669 Bangladesh Journal of Child Health 2009; Vol.33(1): 6-15